RETRACTION Harmanto, H., Setyawan, H., Hamsyah, K., Umar, F., Safrudin, S., Bahriyanto , A., Yeni, M., Ginting , A., Novita , N.., Nurkadri, N., Darmawan, A., HB, G., Pranoto, N. W., & Pavlovic, R. (2024). Integración de la educación para la ciudadanía en las clases de educación física de secundaria en Indonesia: un enfoque para reducir la degradación del carácter (Integrating citizenship education into secondary school physical education lessons in Indonesia: an approach to reducing character degradation). Retos, 60, 865–876. https://doi.org/10.47197/retos.v60.108758 - RETOS, RETOS (Retos, 2025)
Harmanto, H., Setyawan, H., Hamsyah, K., Umar, F., Safrudin, S., Bahriyanto , A., Yeni, M., Ginting , A., Novita , N.., Nurkadri, N., Darmawan, A., HB, G., Pranoto, N. W., & Pavlovic, R. (2024). Integración de la educación para la ciudadanía en las clases de educación física de secundaria en Indonesia: un enfoque para reducir la degradación del carácter (Integrating citizenship education into secondary school physical education lessons in Indonesia: an approach to reducing character degradation). Retos, 60, 865–876. https://doi.org/10.47197/retos.v60.108758 Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that the authorship of the article has been manipulated. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were needed. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. Likewise, a large number of citations and references were manipulated. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI. Authors in the Word document of the article submitted for review: 11 Authors in the published PDF with modified authors: 14 Differences between the authors between both moments: +9 y -6 (Additions: Khairul Hamsyah, Safrudin, Ahmad Bahriyanto, Andarias Ginting, Novita, Nurkadri, Arief Darmawan, Nuridin Widya Pranoto, Ratko Pavlovic. Eliminated: Ari Wibowo Kurniawan, Deasy Wahyuni, Francesca Latino, Francesco Tafuri, Roziah Roziah, Asmiati Asmiati)